PENGARUH E-SERVICE QUALITYDAN HARGA TERHADAP KEPUASAN PELANGGAN: Studi Pada Pengguna Jasa Transportasi Online Grab di Purworejo - Anisa Silvi Rahmawati (STIE Rajawali Purworejo, 2023)
This research aims to examine the influence of e-service quality on customer satisfaction of the Grab online application in Purworejo. In the research, the population was Grab users in the Purworejo Regency area. The number of Grab users is unknown and can be said to be in the infinite category. The sampling technique used is purposive sampling with the hope that the researcher will obtain a representative sample based on the specified criteria. So the total research sample was 97 people. Data analysis techniques use multiple linear regression analysis, determination test, t test and f test. The research results from the multiple linear regression line equation produce the equation Y=-4.136+0.888X1+0.262X2. The constant coefficient value obtained is -4.136. This means that if the value of the e-servicequality and price variables is equal to 0, then the level or magnitude of the customer satisfaction variable is -4.136. The e-service quality variable has a coefficient of 0.888. A value of 0.888 means that if the value of the e-service quality variable increases by 1 unit and other variables are considered constant, the level of customer satisfaction will increase by 0.888. The price variable has a coefficient of 0.262. A value of 0.262 means that if the value of the price variable increases by 1 unit and other variables are considered constant, the level of customer satisfaction will increase by 0.262. Determination analysis produces an Ajusted R Square of 0.837, this figure means that 83% of the level of customer satisfaction can be explained using the e-service quality and price variables. Meanwhile, the remaining 17% may be influenced by other variables that were not studied, for example company image, promotion and brand ambassador factors. The t test shows that the e-service quality variable shows that the calculated t is greater than the t table (12,636> 1,661). This means that hypothesis 1 (H1) proposed that partially there is a significant influence between e-service quality on customer satisfaction is accepted and Ho is rejected. The price variable obtained by t calculated is greater than t table (3267 > 1,661). This means that hypothesis 2 (H2) proposed that partially there is a significant influence between price on customer satisfaction is accepted and Ho is rejected. The f test shows that F count > F table or (247,816 > 3.09) which means Hypothesis 3 (H3) which states that simultaneously there is a significant influence between e-service quality and price on customer satisfaction is accepted and Ho is rejected.